Prognostic factors of palatal adenoid cystic carcinoma: A single‐center analysis of 85 cases - Baoxin Gu; Yanting Chi; Wenjie Wu; Yiwei Zhong; Jianyun Zhang; Jie Zhang (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objective The purpose of this retrospective study was to describe the clinicopathological characteristics of primary adenoid cystic carcinoma (ACC) of the palate and to identify the factors affecting prognosis. Methods The medical records of 85 patients with primary ACC of the palate treated with surgery, with or without adjuvant radiotherapy/chemotherapy, from 2009 to 2019 were reviewed. The relationship of different clinical parameters with locoregional recurrence (LR), distant metastasis (DM), and overall survival (OS) were analyzed. Results Median follow‐up time was 44.6 months. LR and DM rates were 24.7% and 25.9%, respectively, and the 5‐year OS and disease‐free survival (DFS) rates were 85.9% and 55.1%, respectively. Multivariate analysis showed that positive margins were independently associated with the risk of LR (p < .001). Positive margins (p = .001) and high histological grade (p = .031) were significantly associated with shorter OS. Conclusion Positive surgical margins are a strong adverse prognostic factor affecting LR and OS in patients with ACC; apart from that, high histopathological grade is an independent predictor of poor OS. Level of Evidence Level 3 (Prognosis – Cohort study).